ЛИНГВОКОГНИТИВНАЯ И ЛИНГВОКУЛЬТУРОЛОГИЧЕСКАЯ ИНТЕРПРЕТАЦИЯ СИМВОЛА В ХУДОЖЕСТВЕННОМ ТЕКСТЕ - Джусупов, Нурсултан (Studia Rossica Posnaniensia, 2008)
The article presents the integration of linguacognitive and linguacultural aspects of the study of a symbol in the literary text.